Out of Sync & Out of Work : History and the Obsolescence of Labor in Contemporary Culture - Burges, Joel (Book collections on Project MUSE., 2018)
"Out of Sync & Out of Work explores the representation of obsolescence, particularly of labor, in film and literature during a historical moment in which automation has intensified in capitalist economies. Joel Burges analyzes texts such as The Invention of Hugo Cabret, Wreck-It Ralph, Fantastic Mr. Fox, and Iron Council, and examines their "means" of production. Those means include a range of subjects and narrative techniques, including the "residual means" of including classic film stills in a text, the "obstinate means" of depicting machine breaking, the "dated means" of employing the largely defunct technique of stop-motion animation, and the "obsolete" means of celebrating a labor strike. In every case, the novels and films that Burges scrutinizes call on these means to activate the reader's/viewer's awareness of historical time. Out of Sync & Out of Work advances its readers' grasp of the complexities of historical time in contemporary culture, moving the study of temporality forward in film and media studies, literary studies, critical theory, and cultural critique"--